In-Cell Trityl–Trityl Distance Measurements on Proteins - Yang, Yin (J Phys Chem Lett, 2020)
[Image: see text] Double-electron electron resonance (DEER) can be used to track the structural dynamics of proteins in their native environment, the cell. This method provides the distance distribution between two spin labels attached at specific, well-defined positions in a protein. For the method to be viable under in-cell conditions, the spin label and its attachment to the protein should exhibit high chemical stability in the cell. Here we present low-temperature, trityl–trityl DEER distance measurements on two model proteins, PpiB (prolyl cis–trans isomerase from E. coli) and GB1 (immunoglobulin G-binding protein), doubly labeled with the trityl spin label, CT02MA. Both proteins gave in-cell distance distributions similar to those observed in vitro, with maxima at 4.5–5 nm, and the data were further compared with in-cell Gd(III)–Gd(III) DEER obtained for PpiB labeled with BrPSPy-DO3A-Gd(III) at the same positions. These results highlight the challenges of designing trityl tags suitable for in-cell distance determination at ambient temperatures on live cells.